(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Weils disease is a form of a bacterial infection known as leptospirosis that is carried by animals, most commonly in rats & cattle. It can be caught by humans through contact with rat or cattle urine, most commonly occurring through contaminated fresh water. A 53yrs old man presented to the hospital with fever & general weakness, cold, cough, sepsis with acute pyelonephritis. His general tests are normal except the heart rate. Eventually, an ELISA test confirmed presence of leptospira immunoglobulin M. The patient subsequently recovered after a Course of Intravenous Antibiotics. The case of leptospirosis presented to give a note to the general public & health care providers to the clinical importance to the severe disease.